Bioseguridad en odontología ante COVID-19:revisión de aporte a estudiantes y profesionales - Barreto Paredes, Janneth Estefanía (2021)
COVID-19 is a virus that attacks the respiratory tract and can present mild symptoms such as a cold and in some cases cause death. This virus can be transmitted through flugge droplets. In the dental field, transmission can occur by direct contact with patients, through saliva or aerosols produced by the rotary instruments. Therefore, the professional must have knowledge about the protection measures that can prevent the spread of the virus in the consultation. For this, it begins with triage, where a series of questions is asked to the patient to see their health condition, if he has presented any symptoms that make him suspect of COVID-19 or if he has been in contact with someone who has tested positive and determine if his case requires immediate attention. In the case of dental care, the dentist must have all the protective barriers (gloves, mask, gown, cap, shoes, etc.), have knowledge of how they should be placed and how they should be removed, and the correct way to disinfect the dental office and sterilize the instruments. It should also be taken into account the relationship between periodontal disease and coronavirus, what are the preventive measures in these patients and what recommendations can be given.